PERANAN VARIABEL EKONOMI MAKRO TERHADAP INFLASI PASCAPENERAPAN INFLATION TARGETING FRAMEWORK (ITF) 1 DI INDONESIA TAHUN 1999.1-2008.6 - Waluyo, Joko; Ulfah, Ria (Universitas Muhammdaiyah Surakarta, 2010)
The objective of this research is to analyze the effect of macroeconomics variable, which is real exchange rate, SBI, M1 and GDP to domestic inflation in Inflation Targeting Framework. This research also intended to analyze effect of macroeconomics to inflation, which been transmitted through interest rate and will give us a big picture on whatâs the next monetary policies. We used monthly time series data 1999:01â2008:06 and applied Vector Error Correction Model to analyze the phenomenon. Real exchange rate, SBI (quarterly), M1 and GDP have positive effect to the inflation, but only real exchange rate and SBI (quarterly) which has permanent and long term effect. The real exchange rate has strong effect on inflation stability because, by applying ITF. The free-floating exchange rate system should be applied, and the fragile currency shall be easily fluctuated.